Course Advisory System / Lee Chee Siong - Lee, Chee Siong (2004)
Artificial Intelligent is relatively new field in computer science in our country although it has been established for years in other countries. The successful implementation of artificial intelligent methods in a number of domains, especially in advisory domain, has inspired the creation of a Web-based advisory system based on artificial intelligent methods, hence, Course Advisory System (CAS). The main purpose of CAS is to enable STPM students that are applying for courses during the university in-take to get advice through the use of Internet thus given students a better chance of securing a place in university. The system also enables the user to search for synopsis on the courses